“Conviver e sobreviver: família e poder nos sertões do Siará (Banabuiú, séc XVIII)” - Ribeiro, Áurea Regina de Araújo (2022)
The present research analyzes the constitution of a colonial elite in the hinterlands of Banabuiú, in Ceará. The objective is to study the family trajectory of the “Correia Vieira”, perceiving its arrangements and strategies regarding the insertion in the economic and social logic operating in the period, seeking to emerge within the social hierarchy and constitute themselves as local potentates. And for that, they acquired land through allotments and participated in pastoral activity, as well as in a wide web of influences organized around the Banabuiú river. In this sense, it will be necessary to understand the social relationships maintained by the group through the establishment of communication and solidarity networks, which were a differential to obtain the desired interests. Therefore, the bonds made not only by the contacts made, but also from family alliances established through marriages and godfather bonds. In order, to understand the aforementioned dynamics, the spatial approach adopted comprises the territory known as Banabuiú in the Jaguaribe Valley, perceiving it as an important part of the colonial economic dynamics, especially through the livestock system. In view of this, we adopted the temporality between 1700 and 1800, a century capable of providing peculiarities and strong characteristics of a possible development of a conquering elite in the region, justified by permeating the last decades of the 17th century, when one of the most violent wars emerged of conquest fought in the Capitania do Siará, known as “Guerra dos Bárbaros”, the violent combat aimed at the extermination of the indigenous populations of the region. The sources used include, in a special way, the sesmaria dates granted in the Banabuiú river and post-mortem inventories – held by the Arquivo Público do Estado do Ceará (APEC) – and official documents – held by the Arquivo Histórico Ultramarino (AHU), as well as such as baptism and marriage records, genealogies.